2014
DOI: 10.1007/s11695-014-1521-6
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Electrical Stimulation at Acupoints Reduces Body Weight and Improves Blood Glucose in Obese Rats via Autonomic Pathway

Abstract: CEA at ST-36 reduces body weight and improves blood glucose possibly attributed to multiple mechanisms involving gastrointestinal motility and hormones via the autonomic pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…For EA, we used an innovative method, chronic EA, by implanting a pair of electrodes into bilateral ST36 acupoints instead of acutely penetrating acupuncture needles into points. 21 This method has been used for several studies in our laboratory and the advantage of it is that it can avoid stress coming from acupuncture needling, and furthermore it is more inconvenient for repeatable and chronic experiment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For EA, we used an innovative method, chronic EA, by implanting a pair of electrodes into bilateral ST36 acupoints instead of acutely penetrating acupuncture needles into points. 21 This method has been used for several studies in our laboratory and the advantage of it is that it can avoid stress coming from acupuncture needling, and furthermore it is more inconvenient for repeatable and chronic experiment.…”
Section: Discussionmentioning
confidence: 99%
“…A third pair of the electrode wires was implanted into bilateral ST36 (5 mm below head of fibula under knee joint, 2 mm lateral to the anterior tubercle of the tibia of the hind leg) using a previously established method for EA. 21 All connecting wires were tunneled subcutaneously to and brought out at the back of the neck.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Recently, there appears to be a growing interest among researchers on the role of acupuncture in disease prevention and treatment. Some animal studies have found that acupuncture can exert significant effects on the treatment of obesity [2325]. Acupuncture, a time-honored tradition in Chinese Medicine, has been proven to be an effective weight-loss medication.…”
Section: Introductionmentioning
confidence: 99%
“…This is a painful and stressful event to the animal and could induce unwanted stress effects. To resolve these issues, a novel method of EA has been proposed in our laboratory 32 : For animal research, EA is performed using chronically implanted electrodes at acupoints. This would avoid any stress effects each time during the insertion of the acupuncture needle.…”
Section: Discussionmentioning
confidence: 99%